Adhesion characterisation of Portland cement concrete and alkali-activated binders. Issue 2 (15th February 2018) - Phoo-ngernkham, Tanakorn; Hanjitsuwan, Sakonwan; Li, Long-yuan; Damrongwiriyanupap, Nattapong; Chindaprasirt, Prinya
Abstract : Alkali-activated binders (AABs) are investigated for their potential use as repair materials of Portland cement concrete (PCC). The adhesion characterisation of PCC and repair materials using AAB made from fly ash (FA) and Portland cement (PC) activated with sodium hydroxide and sodium silicate solutions, AAB made from FA and calcium hydroxide (CH) activated with sodium hydroxide and sodium silicate solutions, and commercial repair materials (RMs) have been investigated. Test results show that the AAB with additives gives high bond strength which is similar to the use of RMs. Bond strength between PCC substrate and AAB with additives is improved, due to increased reaction products, especially calcium–silicate–hydrate gel. However, the CH replacement at 15% shows a large amount of calcite resulting in a reduction in bond strength. The failure patterns and fracture interface images of the tested specimens also demonstrate the quality of the developed bond strength. It is shown that the interface zone of PCC substrate and AAB is homogeneous with no visible gap between the two bonding surfaces. It is suggested that the AAB with PC as additive can be used as a repair binding material which not only has high bond strength but is also cost-effective.